Genome characteristics of a novel phage from Bacillus thuringiensis showing high similarity with phage from Bacillus cereus. - Yihui Yuan (Public Library of Science (PLoS), 2012)
Bacillus thuringiensis is an important entomopathogenic bacterium belongs to the Bacillus cereus group, which also includes B. anthracis and B. cereus. Several genomes of phages originating from this group had been sequenced, but no genome of Siphoviridae phage from B. thuringiensis has been reported. We recently sequenced and analyzed the genome of a novel phage, BtCS33, from a B. thuringiensis strain, subsp. kurstaki CS33, and compared the gneome of this phage to other phages of the B. cereus group. BtCS33 was the first Siphoviridae phage among the sequenced B. thuringiensis phages. It produced small, turbid plaques on bacterial plates and had a narrow host range. BtCS33 possessed a linear, double-stranded DNA genome of 41,992 bp with 57 putative open reading frames (ORFs). It had a typical genome structure consisting of three modules: the "late" region, the "lysogeny-lysis" region and the "early" region. BtCS33 exhibited high similarity with several phages, B. cereus phage Wβ and some variants of Wβ, in genome organization and the amino acid sequences of structural proteins. There were two ORFs, ORF22 and ORF35, in the genome of BtCS33 that were also found in the genomes of B. cereus phage Wβ and may be involved in regulating sporulation of the host cell. Based on these observations and analysis of phylogenetic trees, we deduced that B. thuringiensis phage BtCS33 and B. cereus phage Wβ may have a common distant ancestor.